History and American public administration - Luton, Larry S. (1999)
As the end of this millennium approaches, American public administration has begun a reexamination of its history. This article examines American public administration's understanding and use of history and suggests improvements in public administration theory that might derive from a more conscientious treatment of history. It begins by framing an understanding of history that does not retreat to the ancient faith in immutable truth but eschews the typical modern dependence on a belief in progress. Many public administration textbooks present the history of American public administration as if it did not really begin until the 1880s, treating the progressive era as the foundation for the eternal varities of public administration. A more inclusive view could be more intelligently critical of progressive era innovations. It could also provide a more complete understanding of who public administrators are and how they can become what they want to be. - Reproduced
Keywords: Public administration - United States; Public administration